2018
DOI: 10.3747/pdi.2017.00274
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Meropenem and Piperacillin/Tazobactam with Heparin in Various Peritoneal Dialysis Solutions

Abstract: This study provides clinically important information on the stability of meropenem and PIP/TZB, each in combination with heparin, in different PD solutions. The use of meropenem-heparin admixed in pH-neutral PD solutions for the treatment of PDAP should be avoided, given the observed suboptimal stability of meropenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Emerging data of piperacillin/tazobactam showed that, when admixed with heparin in dextrose-based and icodextrin-based PD solutions, both drugs are stable for 7 days when refrigerated. 278…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Emerging data of piperacillin/tazobactam showed that, when admixed with heparin in dextrose-based and icodextrin-based PD solutions, both drugs are stable for 7 days when refrigerated. 278…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…11,14,16,19,29 –31 Drug combinations did not cause a significant effect on stability, except for meropenem with heparin in Balance solution which was stable for less than 4 h at body temperature. 31 Meropenem or piperacillin/tazobactam combined with heparin was stable for 3 h at room temperature, but it should be noted that this study assessed stability only at 3 h for this condition. 31 Colouration with or without pH change was observed with the combination of cefazolin and ceftazidime in Extraneal and mixed Balance solution.…”
Section: Resultsmentioning
confidence: 90%
“…In all studies except one, 25 the drug stability was assessed in a PD solution that was contained either in the polyvinyl chloride (PVC) or polyolefin bag. A stabilityindicating assay was utilised in 33% of the studies (n = 7), 12,13,19,23,28,29,31 and an antimicrobial activity assay was reported in 24% of the studies (n = 5). 15,20,22,26,27 Table 1 lists the stability data of b-lactam antimicrobial agents assessed as a single additive to various PD solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the European and United States Pharmacopoeia, stability of an infusate is only given when the drug concentration remains above 90% of the initial concentration during the entire infusion interval [11,12]. Numerous studies have investigated the stability of meropenem in aqueous solutions at various conditions, including antibiotic concentration, temperatures and pH values [13][14][15][16][17][18][19][20][21][22][23]. All these studies focused solely on in vitro stability data.…”
Section: Introductionmentioning
confidence: 99%